Accuracy of Iodine and Calcium Concentrations in Dual Energy Computed Tomography (DECT) (International Journal of Scientific Research in Science and Technology, 2024)
Objective: The purpose of this study was to assess accuracies of iodine and calcium concentrations in dual energy computed tomography (DECT). Method: This study was performed using an in-house phantom made from polyester resin. The in-house phantom had a diameter of 16 cm and had 10 holes filled with iodine (with concentrations of 5, 7.5, 10, and 15 mg/ml), calcium (with concentrations 200, 300, 500, and 600 mg/ml), water, and air. The in-house phantom was scanned by an Ultrafast kV Switching DECT (GE Revolution) with a tube voltage of 80/140 kV, rotation time of 0.5 s, and tube current variations of 200, 250, 300, 335, and 370 mA. Images was reconstructed to a material density image (MDI). The iodine and calcium concentrations were measured using GSI Viewer software and compared with set iodine and calcium concentrations. Results: It was found that absolute percentage error (APE) of concentrations on iodine was
Keywords: dual energy CT; quantification test; phantom